Platinum resistant recurrence and early recurrence in a multi-centre cohort of patients undergoing interval cytoreductive surgery for advanced epithelial ovarian cancer - Bhatt, Aditi; Sinukumar, Snita; Kepenekian, Vahan; Kammar, Praveen; Mehta, Sanket; Shaikh, Sakina; Gertych, Witold; Bakrin, Naoual; Glehen, Olivier (Frontiers in Oncology, 2022)
Background Aggressive locoregional therapies like hyperthemic intraperitoneal chemotherapy(HIPEC) and total parietal peritonectomy(TPP) have been used to delay recurrence in patients with advanced ovarian cancer undergoing interval cytoreductive surgery(CRS). The aim of this retrospective study was to evaluate the incidence of platinum resistant recurrence (PRR) and early recurrence (ER)(recurrence within 6 months and 1 year of the last dose of platinum based therapy, respectively) in patients undergoing interval CRS. The secondary goal was to study impact of each of these therapies on PRR and ER. Methods One-hundred and fifty-three patients undergoing interval CRS from July 2018 to June 2020 were included. The surgical strategy was to perform a TPP in which the entire parietal peritoneum is resected irrespective of the disease extent or a selective parietal peritonectomy (SPP) in which only the peritoneum bearing visible residual disease is resected. The use of HIPEC was at the discretion of the treating oncologists. Results The median surgical PCI was 15 [range, 0-37]. A CC-0 resection was obtained in 119 (77.7%) and CC-1 in 29 (18.9%) patients. Eighty-one (53%) patients had a TPP and 72 (47%) had SPP. HIPEC was performed in 98(64%) patients. Bevacizumab maintenance was administered to 31(19.6%) patients. No patients received PARP inhibitors during first-line therapy. PRR was observed in 8(5.2%) patients and ER in 30(19.6%). The respective incidences of PRR and ER were 4.9% and 16% in the TPP group, 4.1% and 23.6% in the SPP group, 9% and 20% in the no-HIPEC group and 3% and 19.3% in the HIPEC groups. On multivariate analysis, CC-0(p=0.014) resection and HIPEC(p=0.030) were independent predictors of a low ER. All patients with PR and 70% with ER had peritoneal recurrence with or without extra-peritoneal sites of recurrence. Conclusions The incidence of PRR and ER in this cohort was low as compared to historical data. This low incidence could be attributed to the use of aggressive locoregional therapies like TPP and HIPEC. In future, studies should be conducted to confirm these findings and evaluate the potential additive benefit of TPP and HIPEC coupled together as well as their combination with maintenance therapies.